Efficacy of Corticosteroid Injection for Treatment of Trigger Finger: A Meta-Analysis of Randomized Controlled Trials. Issue 5 (4th July 2019) - Ma, Shiwei; Wang, Chunbo; Li, Jiang; Zhang, Zhiyu; Yu, Yao; Lv, Feng
ABSTRACT: Purpose : To determine the efficacy and safety of corticosteroid injection for trigger finger by performing a meta-analysis of all relevant studies. Methods : PubMed, EMBASE, and Cochrane Library databases were searched for randomized controlled trials (RCTs) comparing corticosteroid injection with other treatments for trigger finger. Pooled summary estimates for outcomes, including success rate, relapse rate, visual analogue score (VAS) and complications, were calculated as standardized mean difference (SMD) or relative risk (RR) either on a fixed- or random-effect model via Stata 12.0 software. Results : Ten literatures involving 806 patients (387 in corticosteroid injection group and 419 in control group) were included. Pooled analysis showed there were no differences in the success rate, VAS and complications between patients undergoing corticosteroid injection and others. However, the relapse rate was significantly higher in patients treated with corticosteroid injection than that of other treatments (RR = 19.53, 95% CI = 6.23–61.19). Subgroup analysis indicated the efficacy of corticosteroid injection was superior to other non-surgical treatments (success rate: RR = 1.54, 95% CI = 1.01–2.35), but inferior to surgery (success rate: RR = 0.55, 95% CI = 0.48–0.63; relapse rate: RR = 21.15, 95% CI = 6.06–73.85; VAS: SMD = 3.49, 95% CI = 2.84–4.14). Conclusions : Corticosteroid injection may be an effective strategy for management of trigger finger, although surgery may be needed for some patients due to recurrence.